Rhinopharyngeal autologous fat injection for treatment of velopharyngeal insufficiency in patients with cleft palate - Piotet, Elsa; Beguin, Céline; Broome, Martin; Iglesias, Katia; Olivier, Frédéric; Leuchter, Igor; Zbinden, Chantal; Hohlfeld, Judith; de Buys Roessingh, Anthony; Schweizer, Valérie; Pasche, Philippe (My University, 2015)
Patients with cleft palate are prone to velopharyngeal insufficiency. In minor cases or when hypernasal speech does not resolve after velopharyngoplasty, an augmentation pharyngoplasty with autologous fat can be proposed. The aim of the present study is to evaluate the short-term (within 2 months) and long-term efficiency (during the 24 months following the procedure) of our procedure in the setting of velopharyngeal insufficiency related to a cleft palate. Twenty-two patients with cleft palate related velopharyngeal insufficiency were included in this retrospective study. All patients were operated following the same technique, in the same institution. The pre- and postoperative evaluations included a nasometry, a subjective evaluation using the Borel-Maisonny score, and a nasofibroscopy to assess the degree of velopharyngeal closure. Scores of Borel-Maisonny and nasometry were compared before, shortly after the procedure (within 2 months) and long term after the procedure (within 24 months). Forty-one procedures in 22 patients with a cleft palate performed in our institution between October 2004 and January 2012 were included in the study. Nine patients had a previous velopharyngoplasty with persistent rhinolalia despite intensive speech therapy. In 14 patients the procedure was repeated because of recurrent hypernasal speech after the first injection. The average number of procedures per patient was 1.8. Postoperative nasometry and Borel-Maisonny scores were statistically significantly improved and remained stable until the end of the follow-up (median 42 months postoperative) in most patients. Complications were rare and minor. Autologous fat injection is a simple procedure for treatment of minor velopharyngeal insufficiencies in patients with cleft palate, with good long-term results and few complications.
Keywords: Velopharyngeal insufficiency; Fat injection; Cleft palate; Pharyngoplasty; Autologous fat